Performance Measurement of the Logistics Companies on the Fortune 500 by Swara and Merec-Based Cradis Methods - Özekenci Emre Kadir (Studies in Business and Economics)
The aim of this study is to evaluate the performance of logistics companies on the Fortune 500 Turkey list using the SWARA-MEREC based CRADIS methods. The weight of criteria was determined by subjective and objective approaches, namely SWARA and MEREC, respectively. The performance of companies was ranked by the CRADIS method. The findings highlighted that net sales (NS) and export (EXP) were most and least important criteria, respectively. The result of the CRADIS method showed that Netlog, Borusan and Ekol had the highest performance, while Noatum, BDP International and Horoz had the lowest performance in 2022, respectively. The reliability and robustness of the proposed model was tested with sensitivity and comparative analyses. The results of the sensitivity analysis and comparative analysis showed that the proposed model provides consistent results.